STUDY OF THE ACTION OF AVIATION NOISE IN THE ENVIRONMENTS OF AIRPORT “ELIZOVO” - O. G. Feoktistova; T. V. Naumova; T. G. Feoktistova (Научный вестник МГТУ ГА, 2016)
Investigation of the impact of aircraft noise on the population in the vicinity of the «Elizovo» airport. In the article investigates the impact of aircraft noise on people living near the population in the vicinity of the «Elizovo» airport. Different diseases obtained from noise exposure. The article have been analyzed provides methods and equipment which are used to measure and analyze the results. Inconclusion, the preliminary results obtained in the course of scientific research are cited.